2016
DOI: 10.1080/13543776.2017.1252752
|View full text |Cite
|
Sign up to set email alerts
|

Schiff bases in medicinal chemistry: a patent review (2010-2015)

Abstract: Schiff bases are synthetically accessible and structurally diverse compounds, typically obtained by facile condensation between an aldehyde, or a ketone with primary amines. Schiff bases contain an azomethine (-C = N-) linkage that stitches together two or more biologically active aromatic/heterocyclic scaffolds to form various molecular hybrids with interesting biological properties. Schiff bases are versatile metal complexing agents and have been known to coordinate all metals to form stable metal complexes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
115
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(122 citation statements)
references
References 63 publications
1
115
0
1
Order By: Relevance
“…They are prepared by the condensation between primary amine and active carbonyl compounds . Schiff bases are an important class which are widely used and investigated organic compounds due to their unique properties and numerous applications in many fields including analytical, biological, and inorganic chemistry . Schiff bases form stable complexes with most of transition metals owing to their strong coordinative ability.…”
Section: Introductionmentioning
confidence: 99%
“…They are prepared by the condensation between primary amine and active carbonyl compounds . Schiff bases are an important class which are widely used and investigated organic compounds due to their unique properties and numerous applications in many fields including analytical, biological, and inorganic chemistry . Schiff bases form stable complexes with most of transition metals owing to their strong coordinative ability.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, a group of Schiff base derivatives of THC (Figure ) have been designed and synthesized. Schiff bases are imines which were first synthesized by Hugo Schiff and exhibit a wide range of biological activities such as antimicrobial, antiinflammatory, enzyme inhibitory, and anticancer including DNA damage . Herein the synthesis and in vitro anticancer activity of these Schiff base derivatives of THC are described.…”
Section: Introductionmentioning
confidence: 69%
“…Increased activity results in enhancement in the lipophilicities of the complexes due to delocalization of π-electrons in the chelate ring; it is also reported that increased lipophilicity leads to breakdown of the permeability barrier of the cell. Cu complexes proved to be more active, which may be attributed to higher stability constant than the other complexes [56][57][58].…”
Section: Biological Significance Of Schiff Bases and Their Metallic Dmentioning
confidence: 94%